The Athletic Dream: The Quest for Work Equality in an Unequal Society - Parmer, Twinet; Coleman, Victoria D. (My University, 1994)
African American males have not been afforded adequate access to the work place, and therefore, their work history has been characterized by underemployment and unemployment. However, many African American males have adopted the athletic dream as a path to fame, status, and equality. The purpose of this article was to discuss the quest for equality through the athletic dream in a society where social, cultural and economic factors limit career development and subsequent work experiences.
Keywords: demographics; race; sex/gender; career development; academic support